Efeito do cálcio na qualidade óssea e de ovos de poedeiras - Paz, Ibiara Correia de Lima Almeida [UNESP]; Mendes, Ariel Antonio [UNESP]; Balog, A.; Komiyama, C. M.; Takahashi, S. E.; Almeida, I. C. L.; Garcia, Edivaldo Antonio [UNESP]; Vulcano, Luiz Carlos [UNESP]; Ballarin, Adriano Wagner [UNESP]; Silva, M. C.; Cardoso, K. F. G. (SciELO Espana/Repisalud, 2009)
The experiment was carried out, with hens of the Shaver Brown strain in production, during 27 weeks. The objective was to evaluate the mobilization of bone calcium and phosphorus for the formation of the shell eggs, as well as to follow the variations in the bone quality along the production cycle. 64 birds had been used. The experimental desing was entirely randomized with two treatments (calcium percentage in the diet) and four repetitions of eight birds each. The used diets were isoproteic and isoenergetic adequate (3.8%) and low (1.8%) calcium levels. Analysis of bone (tibiae and femurs) mineral density (DMO) were done at 16, 22, 28, 34 and 40 weeks of age were developed. After each radiographic collection, 4 birds/treatment, were abated for the analysis of bone resistance (RO), Seedor index (IS), dry matter (MS), total mineral (MIN) and calcium and phosphorus (Ca and P). The values of egg production, production of egg mass and quality of the egg shell were also evaluated. It was possible to conclude that the birds mobilized bone minerals for the egg production, independently of the treatment and the birds receiving diets with low levels of calcium had the quality of the eggs shell damaged.
Calcium effect in bone and egg quality of the hens
Keywords: Mineral density; Nutrition; Aves